Relationship between proprioception and balance control among Chinese senior older adults - Wang, Qi; Fu, Haitao (Frontiers in Physiology, 2022)
Background: Balance impairment is the most common risk factor for falls among older adults, with three potential factors (tactile sensation, proprioception, and muscle strength) being responsible for their balance control. However, controversies remain on whether or not balance control is related to the three contributors among older adults. Therefore, clarifying the above questions helps explain the mechanisms of increased falls among senior older adults. This study compares the balance control and the three factors and investigates their relationships among older adults of different ages. Methods: 166 participants ultimately passed the qualification assessment and were categorized into younger (YG, 60–69 years, n = 56), middle (MG, 70–79 years, n = 57), or older (OG, ≥ 80 years, n = 53) aged groups. Berg Balance Scale (BBS) performance, tactile sensation, proprioception, and muscle strength were tested. One-way ANOVA and partial correlation were performed to explore the differences between groups in BBS and its three potential contributors, along with the correlations between them within each age group. Results: Significant differences among the three groups were detected in BBS scores (p<0.001), tactile sensation at the great toe (p=0.015) and heel (p=0.025), proprioception of knee flexion (p<0.001) and extension (p<0.001), and ankle plantarflexion (p<0.001) and dorsiflexion (p<0.001), and muscle strength of ankle plantarflexion (p<0.001) and dorsiflexion (p<0.001), and hip abduction (p<0.001). Proprioception of knee flexion (r=-0.351, p=0.009) and extension (r=-0.276, p=0.041), and ankle plantarflexion (r=-0.283, p=0.036), and muscle strength of ankle plantarflexion (r=0.326, p=0.015) and hip abduction (r=0.415, p=0.002) were correlated with BBS among the YG. Proprioception of ankle plantarflexion (r=-0.291, p=0.030) and muscle strength of ankle plantarflexion (r=0.448, p=0.001) and dorsiflexion (r=0.356, p=0.007) were correlated with BBS among the MG. Muscle strength of ankle plantarflexion (r=0.276, p=0.039) and hip abduction (r=0.324, p=0.015) were correlated with BBS among the OG. Conclusion: YG and MG had better balance control, tactile sensation, proprioception, and muscle strength compared to OG. Proprioception correlated with balance control in YG and MG, but not in the OG. The worsen proprioception among the OG could be the key for increased falls. Exercise should be recommended to improve proprioception among senior older adults.